Structural and floristic pattern in a disturbed mangrove tropical swamp forest: a case study from the Langkawi UNESCO Global Geopark Forest, Peninsular Malaysia - Wan Norilani Wan Ismail,; Wan Juliana Wan Ahmad,; Muhammad Razali Salam,; A. Latiff, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Forest structure, diversity and above-ground biomass assessment are important to understand the structural and floristic dynamics of a mangrove forest ecosystem. Our study provides valuable comparative analysis between two areas of disturbed mangroves at Kisap Forest Reserve, Langkawi Island. The two study sites were swamp forest at C5 which was disrupted by harvesting activities for charcoal production and C7 was disturbed by lightning strikes. A total of 1,217 and 390 trees measuring 1 cm diameter and above were enumerated in 0.25 ha plots at both sites. Seven mangrove plant species in C5 and eight in C7 were recorded. Ceriops tagal and Rhizophora apiculata were the most prominent species in the C5 and C7, respectively, whereby the Rhizophoraceae was the densest family at both sites. The major contributor of total basal area at C5 and C7 were C. tagal (5.02 m2/ha) and R. apiculata (11.14 m2/ha). Similarly, C. tagal (22.41 t/ha) and R. apiculata (111.75 t/ha) also contributed the highest biomass in C5 and C7, respectively. Diversity and species richness were higher at C7 H’=1.22; R’=1.17 compared to C5 H’= 0.76; R’=0.85 and low evenness at both sites. High similarity was indicated between the two sites by 93%. The distribution of individuals in C7 was homogenous than that of C5, which had more saplings. In conclusion, anthropogenic activities resulted in lower productivity of forest compared to natural disturbances.